THE EVOLUTION OF PROJECT MANAGEMENT METHODS AND TOOLS IN THE CONTEXT OF NEW MANAGERIAL TURBULENCE - Галушка, Зоя (SWorldJournal, 2025)
The article explores the evolution of project management methods and tools in the context of new managerial turbulence, characterized by high instability, fragmented regulatory environments, digital asymmetry, and shifts in the social structure of teams.